تقييم مدى التزام شركات التأمين السورية بمبادئ الحوكمة "دراسة مسحية على شركات التأمين الخاضعة لإشراف هيئة الأوراق والأسواق المالية السورية" - زاهر, بسام; دريباتي, يسيرة; بركات, حيان محمد (Latakia University Journal - Economic and Legal Sciences Series, 2013)
تهدف الدراسة إلى تسليط الضوء على مفهوم حوكمة الشركات, ومدى أهميّتها, وما هي العوامل التي تلعب دورا في نجاح تطبيقها, بالإضافة إلى تقييم مدى التزام شركات التأمين السورية الخاضعة لإشراف هيئة الأوراق والأسواق المالية السورية بمعايير وأسس الحوكمة التي وضعتها منظّمة التعاون الاقتصادي والتنمية عام 2004 وهي: ضمان وجود أساس لإطار فعّال لحوكمة الشركات, حماية حقوق المساهمين, ضمان المعاملة المتكافئة للمساهمين, ضمان حقوق أصحاب المصالح, الإفصاح والشفافية, مسؤوليات مجلس الإدارة. تمّ في الدراسة استخدام المنهج الوصفي التحليلي من خلال استعراض مفهوم الحوكمة وأسباب الاهتمام بها واستعراض لمحدداتها, تمّت الدراسة الميدانيّة على سبع من شركات التأمين الخاضعة لإشراف هيئة الأوراق والأسواق المالية, ومن أجل تحقيق أهداف الدّراسة تمّ توزيع استبيان, وتحليل الإجابات باستخدام برنامج SPSS. خَلُصت الدراسة إلى أنّ هناك مستويات جيدة من تطبيق الحوكمة في شركات التأمين محل الدراسة ويعطي هذا مؤشرا جيدا على وجود نظرة إيجابية من قِبَل هذه الشركات لأهمية تطبيق الحوكمة, كما أوصت الدراسة بضرورة توحيد جهود الجهات الإشرافية في مجال تطبيق الحوكمة, وحثّ شركات التأمين السورية للانتقال من مرحلة الالتزام بالمعايير الموضوعة من قبل الجهات الإشرافية إلى مرحلة السعي لوضع مبادئ حوكمة خاصة بها بما يساعد في زيادة فعالية التطبيق, كما أوصت الدراسة بضرورة الاستفادة من تجربة تطبيق الحوكمة لدى هذه الشركات من أجل تعميم النتائج على شركات التأمين الاخرى تمهيدا لإدراجها في سوق الأوراق المالية. The research aims to enlighten what corporate governance means and its importance, and what are the aspects that take place in achieving it. Also, it aims to evaluate the commitment of the Syrian insurance companies under the supervision of the Syrian Securities Commission and Financial Markets to the corporate governance standards and foundations established by the Organization for Economic Cooperation and Development in 2004, which are: Ensuring the basis for an effective corporate governance framework, the rights of shareholders and key ownership, functions, the equitable treatment of shareholders, the role of stakeholders in corporate governance, disclosure and transparency, and the responsibilities of the board. In this study, the descriptive analytical approach was used by reviewing the concept of governance and the reasons that led to increase interest in it with a review of its determinants. The study took place in seven of the insurance companies which are subject to the supervision of the Commission on Financial Markets and Securities. A questionnaire has been distributed to achieve the goals of this study and analyze the received answers using the statistical techniques by SPSS. The study concluded that there are good levels of application of corporate governance in insurance companies under study, and this gives a good indication of the existence of a positive outlook by these companies of the importance of the application of corporate governance. The study also recommended the need to unify the efforts of the various supervisory authorities in the application of corporate governance, and urged insurance companies to move from the stage of commitment to standards set by the supervisory authorities to the stage of seeking to develop its own governance principles in a way that help to increase the effectiveness of the application. The study also recommended the need to benefit from the experience of the application of corporate governance in these companies in order to disseminate the results to other insurance companies, in preparation for inclusion in the Stock Market.